ANALISIS KADAR TIMBAL (Pb) DAN ARSEN (As) PADA AIR GAMBUT DI DESA RASAU JAYA KABUPATEN KUBU RAYA - Syari, Jajar Pramata (Jurnal Laboratorium Khatulistiwa, 2023)
One of the abundant water resources on the island of Kalimantan is peat water, because peatlands are widely distributed in West Kalimantan, especially in Kubu Raya Regency. Residents living in peat swamps in parts of Kalimantan, especially in the area of Rasau Jaya Village, Kubu Raya Regency, use peatlands as a residence and land for plantations and agriculture, so that they use dug wells in the form of peat water and are widely used by local residents to carry out daily activities days such as washing, bathing, cooking and so on. Heavy metals in the form of Pb and As are pollutants that are difficult to degrade and even tend to accumulate in the body of exposed living things. The purpose of this study was to analyze the content of Pb and As metals in peat water in Rasau Jaya Village, Kubu Raya Regency. The research design used is descriptive method. The population in this study was peat water in the area of Rasau Jaya Village, Kubu Raya Regency. A sample of 10 peat well water samples from the Dusun Kebun Jeruk residents, Rasau Jaya Village, Kubu Raya Regency. The results were obtained based on Permenkes RI RI No. 32 of 2017 Concerning Environmental Health Standard Quality Standards and Water Health Requirements for Hygiene, Swimming Pool, Solus Per Aqua, and Public Baths used for clean well water samples that met 40% quality standards, namely Well 3, 6, 8 and 9.